1991
DOI: 10.1038/ki.1991.21
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intravenous infusion of atriopeptin 3 on immediate renal allograft function

Abstract: Thirty-eight recipients of nineteen pairs of cadaveric kidneys were entered into a double-blind randomized study in which one recipient received a 12-hour intravenous infusion of Atriopeptin III (AP-3), a synthetic analogue of atrial natriuretic factor, commencing at release of the vascular clamps, and the other received a placebo infusion. In an initial dose ranging study, successive groups of six kidneys (3 pairs) were randomized to receive each of 0.0125, 0.025, 0.05 micrograms/kg/min AP-3 or placebo. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…It is likely that cyclic GMP, a second messenger induced by NO, is elaborated by the kidney during IL-2 therapy (68,73,74). It has been shown that atrial natriuretic factor, a peptide with vasodilating and diuretic/natriuretic properties, ameliorates, via cyclic GMP, the severity of acute renal failure (75,76).…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that cyclic GMP, a second messenger induced by NO, is elaborated by the kidney during IL-2 therapy (68,73,74). It has been shown that atrial natriuretic factor, a peptide with vasodilating and diuretic/natriuretic properties, ameliorates, via cyclic GMP, the severity of acute renal failure (75,76).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 18 studies were further excluded, since they involved evaluation in nonsolid organ transplant setting. Our analysis finally identified 7 eligible studies comprising total 238 participants (118 natriuretic peptide group; 120 control group) [4, 6, 22–26]. Characteristics of the included studies are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Mean age of the participants was 44 years and 40% participants were females. Four studies (135 participants) evaluated the role of human atrial natriuretic peptide [4, 6, 23, 26]. Three studies (103 participants) evaluated the role of urodilatin [22, 24, 25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been several negative studies of prophylactic ANP therapy; for example, ANP failed in two studies to prevent primary renal transplant dysfunction 228, 229 and ANP prophylaxis also failed to prevent CI-AKI. 230 Based on the positive results of small clinical studies using ANP to treat AKI, a randomized placebo-controlled trial in 504 critically ill patients with AKI was conducted.…”
Section: Rationalementioning
confidence: 99%